Successful management of patent ductus arteriosus in severely malnourished boy - Dyahris Koentartiwi (Universitas Syiah Kuala, 2021)
Background: Patent ductus arteriosus is a vascular structure that connects the proximal descending aorta to the roof of the main pulmonary artery near the origin of the left branch pulmonary artery results in congestive heart failure, pulmonary hypertension, recurrent pneumonia and severe malnutrition. Transcatheter closure of PDA usually performed for the body weight above 6 kilograms, this is our first case in our hospital to close PDA in a child with the body weight less than 6 kilograms with satisfactory result.